2022
DOI: 10.3390/ijms23031762
|View full text |Cite
|
Sign up to set email alerts
|

A Major Intestinal Catabolite of Quercetin Glycosides, 3-Hydroxyphenylacetic Acid, Protects the Hepatocytes from the Acetaldehyde-Induced Cytotoxicity through the Enhancement of the Total Aldehyde Dehydrogenase Activity

Abstract: Aldehyde dehydrogenases (ALDHs) are the major enzyme superfamily for the aldehyde metabolism. Since the ALDH polymorphism leads to the accumulation of acetaldehyde, we considered that the enhancement of the liver ALDH activity by certain food ingredients could help prevent alcohol-induced chronic diseases. Here, we evaluated the modulating effects of 3-hydroxyphenylacetic acid (OPAC), the major metabolite of quercetin glycosides, on the ALDH activity and acetaldehyde-induced cytotoxicity in the cultured cell m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…This microbial-derived metabolite has showed antihypertensive and anti-cytotoxic effects, depending on the gut dysbiosis condition. [72,73] Therefore, the levels of these two interesting metabolites can be affected by the photoperiod via gut microbiota composition, as it can be influenced by the photoperiod. [23,36] Interestingly, these effects were significantly less prominent when treating with ABX.…”
Section: Discussionmentioning
confidence: 99%
“…This microbial-derived metabolite has showed antihypertensive and anti-cytotoxic effects, depending on the gut dysbiosis condition. [72,73] Therefore, the levels of these two interesting metabolites can be affected by the photoperiod via gut microbiota composition, as it can be influenced by the photoperiod. [23,36] Interestingly, these effects were significantly less prominent when treating with ABX.…”
Section: Discussionmentioning
confidence: 99%
“…Establishment and validation of the XRE-NanoLuc luciferase reporter assay using the XRE-NLuc::HaCaT cell line To determine the potential effect of FG1 on the xenobiotic response caused by AhR, we generated a HaCaT human keratinocyte cell line stably expressing NanoLuc luciferase under three XRE motifs (CACGC) (Fig. 2a: vector map; 2b: cell image) 23 . The e cacy of this cell line was veri ed using established XRE activators (AhR ligands), such as 6-formylindolo (3, 2-b), carbazole (FICZ), indirubin (IND), 2-(1'H-indole-3'-carbonyl)-thiazole-4-carboxylic acid methyl ester (ITE), and indole-3-carbinol (I3C) 24 .…”
Section: Resultsmentioning
confidence: 99%
“…3,4-Dihydroxyphenylacetic acid (DOPAC) and 3-hydroxyphenylacetic acid (OPAC) are the major intestinal catabolites of the quercetin glycosides produced by the gut microbiota 23,25) . We demonstrated that DOPAC and OPAC each significantly protected the cells from the acetaldehyde-induced cytotoxicity with the enhanced total ALDH activity through the transcriptional regulation 26,27) . On the other hand, there is a significant difference in the antioxidant activities between DOPAC and OPAC, even though their chemical structures are quite similar to each other.…”
Section: (2) Intestinal Catabolites Of Quercetin Glycosidesmentioning
confidence: 91%